Distribution of Seismic Damage in Steel Buildings Component Equipped by Viscoelastic Dampers against Far-Field Earthquake - Yaser Parvin Darabad; Alireza Hassanpour Yasaghi; Beniamin Khodaei; Reza Zarei (Shock and Vibration)
Damage to structures with the concept of inelastic behavior and consequently hysteresis energy is very close. Therefore, it can be said that hysteresis energy at these levels can be a significant criterion for designing or controlling the structure. In this research, the first three steel frames of 4, 8, and 12 floors with the medium bending frame system have been designed with the statically equivalent method according to valid international regulations; then, all frames have been subjected to nonlinear dynamic analysis by seven accelerometers. The purpose of this study is to investigate the distribution of damage, energy, relative displacement, roof displacement, and base shear in the studied frames. In the following, the necessity of using the retrofitting method to reduce the relative displacement is described based on the regulations. Then, viscoelastic dampers are used to strengthen and reduce damage in the studied frames in the face of distant field records. The obtained results indicate that despite the uniform distribution of resistance in the height of the floors, the hysteresis energy distribution and damage diagrams do not follow this distribution and other parameters such as hysteresis energy, which play a major role in structural members’ damage, should be included in the design process. In this research, viscoelastic dampers have been used for retrofitting. The results show that this type of damper shows good performance in reducing damage under earthquakes in the remote area.